BASIC CONCEPTS OF DETERMINING THE CRACK RESISTANCE OF REINFORCED CONCRETE STRUCTURES BY THE PRINCIPLE OF FRACTURE MECHANICS - Luchko, Й.; Bodnar, Ю. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
This paper presents the generalized results of the analysis and synthesis of scientific and technical sources on studying heavy concrete and reinforced concrete structures and buildings based on the fracture mechanics principles. The research results on the crack resistance of concrete and reinforced concrete structures over the last 25–30 years are presented. The occurrence and normal cracks development conditions and the various influence factors that testify to the benefit of fracture mechanics methods are set up. In particular, a method of calculating the stress intensity factor for beam structures with bending cracks is developed. In addition, the moments of crack formation and cracks opening in steel-reinforced concrete slabs are determined. A method of crack resistance during long-term bending, taking into account the creep and shrinkage of concrete, is developed. Calculation results are compared with experimental data. Calculation models and solved problems on the formation and subcritical growth of cracks in a non-stationary setting are formulated. A method of calculating the forces in the rod reinforcement around the crack is developed. The moment of crack formation and calculation of crack opening using the methods of the mathematical theory of cracks and other aspects of calculating such structures is determined. The results of theoretical and experimental studies of the long-term reinforced concrete structures on reliability and durability and assessing a residual resource are summarized too. On the basis of the generalized data given in the publications, the methods of technical diagnostics and repair and restoration work with strengthening are worked out. It enables increasing the resource and reliability of the reinforced concrete buildings and structures.